PENGARUH SIFAT TANAH DAN CURAH HUJAN TERHADAP PRODUKTIVITAS PADI SAWAH DI KABUPATEN BANTUL - , SITI MARO'AH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rice is the main commodity of Indonesia. Increasing of population causes increasing request to it. Bantul is a district in Yogyakarta Province which cultivates the rice field. Problem in the land of rice field is the diminishing of productivity influenced by soil properties and rainfall. This research aims to provide information about the influence of soil properties and rainfall on the productivity of rice field. Result of the research showed that the soil properties significantly influence productivity of rice field, i.e. available K, pH H2O, total N, Clay, organic-C, CEC and available P. Rainfall does not significantly influence the whole rice field productivity, however rainfall significantly influence productivity of rice field at each planting season. Irrigation is needed to meet the water requirement at the time water is deficient due to low rainfall.